Biodiesel Production from Waste Palm Oil Catalyzed by Hierarchical ZSM-5 Supported Calcium Oxide - Yusuf Muhammad Zein; Anil Kumar Anal; Didik Prasetyoko; Imroatul Qoniah (Universitas Gadjah Mada, 2016)
Biodiesel production from waste palm oil catalyzed by hierarchical ZSM-5 supported calcium oxide was studied. The activity of CaO increased after supported on h-ZSM-5 resulting an increase in conversion from 93.17% to 95.40%. A maximum conversion of 95.40% was achieved at 6 h reaction time, 3 wt.% catalyst amount, 12:1 methanol to oil molar ratio and 65 °C reaction temperature. The waste palm oil showed a high potential as a feedstock in biodiesel production in which there was no significant different in the conversion of fresh and waste palm oil. The properties of the obtained biodiesel required the limits of biodiesel specification according to ASTM D6751-08 and EN 14214 with the methyl ester content of 97.18%, the acid value of 0.24 mg KOH/g, the kinematic viscosity of 4.64 cSt and the density of 869.9 kg/m3.